Relationship Job Satisfaction With Turnover Intention On Nurses In The Inpatient Ward Of A Private Hospital Batam City In 2020 - Didi Yunaspi; Fransiska Mariona Nova; Roza Erda; Afif D Alba (Institute of Computer Science (IOCS), 2021)
American Health Care Association revealed that from the total turnover rate of 35.1%, an increase of 39.5%, this data shows that there was the highest increase in nursing staff by 4%. Research in the United States, Canada, UK, and Germany shows that 41% of nurses in hospitals are dissatisfied with their jobs and 22% of them plan to leave their jobs within one year. One of the factors that affect turnover intention to nurses is job satisfaction. This study aims to determine the relationship between job satisfaction and turnover intention of nurses in patient room Private Hospital, using an analytical study with a cross sectional design. The number of nurses in the study was 51 nurses. The data analysis used was the Kruskall Wallis test, Kruskall Wallis statistical test results obtained value (p value = 0.003 <0.05), indicating that Ho is rejected and Ha is accepted. Conclusion: There is a significant relationship between job satisfaction and turnover intention for nurses in the inpatient room of Private Hospital, Batam City in 2020. Hospital management is expected to make a policy to minimize the increase in turnover and increase nurse job satisfaction